COLLECTIVE MEMORY AND MEMORY POLITICS IN THE CENTRAL CAUCASIAN COUNTRIES - GARAGOZOV, Rauf (CENTRAL ASIA AND THE CAUCASUS, 2005)
The recent media reports1 about the progress made by a group of academics from Armenia, Russia, Georgia, and Azerbaijan working on a joint textbook on the history of the Caucasus from the ancient times to 1921 revealed how much tension this topic has created in the region. The project known as the Tbilisi Initiative launched in 1997 was encouraged and funded by the Council of Europe within a program for promoting education reforms in the former Soviet republics. This work designed to provide objective and reliable information about the local nations’ past was expected to help develop tolerance and openness and overcome xenophobia, prejudice, nationalism, chauvinism, etc.2 The published interview,3 however, revealed that the dis agreements about the interpretations of history were too deep to be overcome: each national team set about writing its own history of the Caucasus. This symbolic fact opened up a large layer of cultural, historical, political, and other aspects typical of the region that normally remains concealed. This shows that the sides cannot agree on an interpretation of even their distant past, to say nothing of the present. In the present context of ethnic conflicts and war, it would be too much to expect the project to be an instant success: too many regional conflicts were accompanied by what is known as a “war of historians,”4 in which historical facts were retrieved from archives to justify territorial claims. In other words, in Caucasian history is part of today’s politics; and the stakes are too high to expect the project to succeed in the near future.